新加坡初级学院学生 “是……的” 句式的使用情况 = The use of shi...de by Singapore junior college students - 刘敏仪 Liew, Mun Yee (Nanyang Technological University, 2020)
在现代汉语中，“是……的”强调句式是常见又特殊的表达句式。其作用在于让说话者准确表达句子的重心，让听者迅速捕捉关键讯息，以达到有效的沟通。虽然使用频率高，但汉语学习者却屡屡出现使用偏误的现象。而针对“是……的”偏误现象的研究，许多学者都着重于美国、澳洲、英国等英语为母语的汉语学习者，以新加坡学生为对象的研究却寥寥无几。为了理解新加坡学生对“是……的”句式的掌握程度，本研究通过收集新加坡初级学院学生的作文语料，分析其偏误类型，并且结合新加坡语言环境的概况，探讨出现偏误的可能原因。研究结果显示，在使用“是……的”句式时：（一）新加坡学生最常出现的偏误类型是“缺省”，其中又以缺省“的”的现象最严重。（二）在英语强调句式负迁移的影响下，新加坡学生无法彻底掌握“是……的”句式的使用规则，对“的”的用法尤其不理想。（三）新加坡学生所采取的简化和回避策略，加剧了“缺省”偏误现象。希望本研究能为新加坡教育工作者在“是……的”句式教学上提供参考，提升新加坡学生对“是……的”句式的掌握程度，以达到更有效地沟通。The shi…de construction in Mandarin Chinese functions to identify the focus of a message conveyed by the speaker. Albeit how common and frequent this construction is used in Mandarin, the construction is often used with errors by Mandarin learners. Current studies on the misuses of the shi…de construction are mainly targeted at Mandarin learners from English speaking countries like the US, Australia, and UK. Little research has been conducted among students in Singapore.This study aims to analyse the usage of shi…de among junior college students in Singapore based on their writing samples. The research focuses on the types of erroneous usage, taking into account the Singapore context, and discusses the possible causes leading to the errors. There are three major findings in this study: 1. Omission is the most frequent error among Singapore students; more specifically, the missing of de in the construction is the most commonly seen error. 2. The negative transfer of English focus construction into Mandarin may have affected the students’ command of shi…de. 3. The adoption of simplification and deliberate avoidance strategies may have also contributed to the omission errors.This thesis hopes to serve as a reference for the teachings of the shi…de construction in Singapore. And ultimately, to improve students’ command of it for more effective communication.